Reliability of BOLD signals in chronic stroke‐induced aphasia. (28th April 2020) - Higgins, James; Barbieri, Elena; Wang, Xue; Mack, Jennifer; Caplan, David; Kiran, Swathi; Rapp, Brenda; Thompson, Cynthia; Zinbarg, Richard; Parrish, Todd
Abstract: Investigating the neurobiology of language impairment and treatment in chronic stroke aphasia using fMRI requires an understanding of measurement variability within and between participants. In this multicenter study, we evaluated the scan–rescan reliability of an auditory and visual (written) story comprehension paradigm in stroke participants with aphasia ( N = 65) and healthy controls ( N = 22). The multi‐modal task was conducted twice ( 1 week apart) on separate visits upon study enrolment and twice again at completion three months later. A non‐language visuomotor task was studied in the aphasia group only, which was conducted once per time point (3 months apart). While participants were asked to make responses during the comprehension task, these in‐scanner responses were not recorded. Reliability was assessed using intraclass correlation coefficient (ICC) at both group and individual participant levels. The visual story comprehension condition had higher reliability than the auditory condition in both groups, with participants with aphasia exhibiting lower reliability than controls in both conditions (stroke ICC = .43, healthy ICC = .81). Differences in reliability within the group of participants with aphasia were found to be partially explained by overall language impairment as well as greater head motion. In the participants with aphasia, the visuomotor paradigm was found to have greater reliability than the story comprehension task at equivalent interscan intervals (visuomotor = 0.50, comprehension = 0.34), and its reliability was not associated with language impairment. This work highlights the importance of considering the reliability of fMRI tasks in aphasia research, provides strategies to improve reliability and has potential implications for the field of clinical neuroimaging in general. Abstract : A language fMRI task was conducted in healthy controls and participants with stroke aphasia, and scan–rescan reliability was assessed using intraclass correlation. A non‐language visuomotor paradigm was used as a comparison in the participants with aphasia. Within‐subject language reliability was lower in the participants with aphasia, and lower reliability was related to greater disorder severity, larger amounts of head motion, and differed by stimulus modality (visual versus auditory stories).